TRANSFORMASI TRADISI PERNIKAHAN ADAT TUNGGU TUBANG PADA MASYARAKAT SEMENDE DESA CAHAYA ALAM MUARA ENIM TAHUN (2010-2025) - Nismaharani Nismaharani; Farida R Wargadalem; Helen Susanti (Yayasan Literasi Sains Indonesia, 2026)
The tunggu tubang tradition is a custom granting the eldest daughterupon marriagethe right to manage her parents' inheritance, care for her parents, and look after her siblings until they become independent; this tradition also shapes marriage practices and the community's social structure. This article aims to examine the procedures of the tunggu tubang marriage tradition within the Semende community and the changes this tradition underwent between 2010 and 2025. The study employs a qualitative descriptive method utilizing a social approach, interviews, documentation, literature reviews, and fieldwork. The findings reveal that the tunggu tubang marriage tradition involves a series of required processes. These consist of two stages: pre-wedding traditions including matchmaking perjodohan, the formal proposal naikkah rasan, dowry negotiation, the formation of event committees by both the groom's and bride's families, the presentation of a buffalo and cooking spices, a poetic exchange, and a shawl tossing ceremony and the wedding ceremony stage itself, comprising the solemnization of the marriage, the ceremonial serving of traditional cakes, the wedding reception, and the ceremonial escorting of the bride to and from the groom's family home. However, around 2010, several traditions such as matchmaking, the shawl-tossing ceremony, the ritual (replaced by a cash payment), and the ceremonial serving of cakes were largely abandoned. This shift was driven by factors including the changing times, the desire for practical wedding arrangements, and financial considerations, as the tunggu tubang marriage tradition was perceived to symbolize opulence.